2016
DOI: 10.1186/s40959-016-0019-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular co-morbidity in cancer patients: the role of psychological distress

Abstract: Due to aging of the population and cardiotoxic cancer treatment, there is an increasing group of patients with cancer and co-morbid cardiovascular disease (CVD). In order to find a balance between the risk of undertreating the malignancy on the one hand and inducing CVD on the other hand, CVD risk stratification at the time of cancer diagnosis and knowledge on the pathway for developing incident CVD in cancer patients is vital. In this paper, we propose an adapted multiple-hit hypothesis for developing CVD in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 57 publications
2
17
0
3
Order By: Relevance
“…Third, research within the field of cardiology has suggested that individuals who experience high levels of stress, or experience symptoms of depression or anxiety have an increased risk of incident CVD . It is well known that both a diagnosis of cancer and its associated treatment may increase stress, anxiety, and depression, which could potentially exacerbate the risk of incident CVD in cancer survivors …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, research within the field of cardiology has suggested that individuals who experience high levels of stress, or experience symptoms of depression or anxiety have an increased risk of incident CVD . It is well known that both a diagnosis of cancer and its associated treatment may increase stress, anxiety, and depression, which could potentially exacerbate the risk of incident CVD in cancer survivors …”
Section: Discussionmentioning
confidence: 99%
“…28 It is well known that both a diagnosis of cancer and its associated treatment may increase stress, anxiety, and depression, 26,29,30 which could potentially exacerbate the risk of incident CVD in cancer survivors. 6,31 By correcting for the presence of traditional cardiovascular risk factors prior to cancer diagnosis, and by using a strict definition of CVD, we may be missing the precursors of CVD and thus underestimate the risk of CVD in cancer survivors. Our finding that the increased CVD risk among prostate cancer survivors compared to matched cancer-free controls was limited to those who did not have any traditional cardiovascular risk factors prior to their cancer diagnosis is interesting.…”
Section: Fully Adjusted Hr (95% Ci)mentioning
confidence: 99%
See 2 more Smart Citations
“…Prevalence rates for anxiety and depression range from 15% to 27%, hence one in every five prostate cancer survivors are afflicted [14,15]. Consequently, prostate cancer survivors may have an increased risk of incident CVD if only by these elevated levels of psychological distress after cancer diagnosis [16]. Indeed, a study by our group amongst breast cancer survivors showed that pharmaceutically treated anxiety prior to cancer diagnosis increases the risk of incident CVD, while controlling for depression, traditional cardiovascular risk factors, and clinical factors [17].…”
Section: Introductionmentioning
confidence: 99%